Disrupting Colonial Narratives of Place: The q̓íc̓əy̓ Slough Yesterday, Today, and Tomorrow Project - Hill, Cher; Bailey, Rick; McKay, Carman (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2024)
What happens when traces of the past are invited to "haunt" the present, disrupting the colonial narratives inherent in local spaces, and creating openings for new stories and new relationships? Guided by Indigenous and post-human worldviews, this action-research project facilitated community learning about the q̓íc̓əy̓ (Katzie) Slough, while collectively imagining new futures for this waterway. Elementary students learned from Elders and environmentalists at the Slough, while simultaneously caring for the land. They then made art with the land, which, along with Elder stories, guided the creation of a school mural. The teachings of the mural and the children’s art continue to reverberate as their stories are shared with post-secondary students and teachers. This research informs how we might engage learners with the complexities and complicities of settler colonialism and provides an example of a local land-centred curriculum that informs how we might all live well together, contributing to real world change.